Earl Hines and "Rosetta" - Taylor, Jeffrey (Current Musicology, 2001)
One of the proudest moments of Earl "Fatha" Hines's career took place in 1976, when he was invited to perform at a White House dinner in honor of the President of France. Mter an evening chatting with Betty Ford and Clint Eastwood, Hines sat down at the piano in the East Room and launched into "Rosetta."